THE CONCEPT OF ZAKAT AND WAQF IN MIR'AT AL THULLAB - Al-Ayubi, Solahuddin; Shalehanti, Nadhia; Sakti, Ali (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2022)
This research aims to explain the concept and practice of zakat and waqf in the Book of Mir'at al Thullab. This research uses a formal literature study method in explaining the concept of zakat and waqf in the Book of Mir'at al Thulab using economic analysis and a historical approach. Indonesia as a country with the largest Muslim population in the world has great potential in the use of social funds, especially zakat and waqf in order to reduce inequality and poverty that occurs due to the uneven distribution of wealth. However, zakat and waqf management in Indonesia has not been managed and utilized optimally. The Book of Mir'at all Thullab by Sheikh Abdurrauf As Singkily, which is used by the Sultanate of Aceh Darussalam and other sultanates in Indonesia, can be a historical reference for optimizing zakat and waqf in the welfare of the people. The Book of Mir'at all Thullab provides valuable information and lessons in optimizing zakat and waqf, such as the role of special institutions as amil and the use of qadi or penghulu in zakat management throughout the country. In addition, the sultanate through the Baitulmal institution always announces the collection time in the month of Muharram, so that public awareness is maintained. In management, the use of zakat and waqf is used for consumptive and productive purposes of the duafa community which helps the needs and improves the living standards of the duafa community.